Applied statistics for engineers and physical scientists - Ledolter, Johannes, ....-; Hogg, Robert Vincent, 1924-2014 (Upper Saddle River (N.J.) : Pearson/Prentice Hall, 2010)
This hugely anticipated revision has held true to its core strengths, while bringing the book fully up to date with modern engineering statistics. Written by two leading statisticians, Statistics for Engineers and Physical Scientists,3/e, provides the necessary bridge between basic statistical theory and interesting applications. Readers solve the same problems that engineers and scientists face, and have the opportunity to analyze real data sets. Larger-scale projects are a unique feature of this book, which let readers analyze and interpret real data, while also encouraging them to conduct their own studies and compare approaches and results. This book assumes a calculus background. Collection and Analysis of Information; Probability Models and Discrete Distributions; Continuous Probability Models; Statistical Inference: Sampling Distribution, Confidence Intervals, and Tests of Hypotheses; Statistical Process Control; Experiments with One Factor; Experiments with Two or More Factors; Regression Analysis.
Includes bibliographical references and index.
Keywords: Engineering -- Statistical methods